Generation mean analysis in maize (Zea mays) for yields and yield attributing traits - SHARMA, PREETI; KAMBOJ, MEHAR CHAND; SINGH, NARENDER; KUMAR, RAMESH; KUMAR, NAVEEN (The Indian Journal of Agricultural Sciences, 2022)
The nature of gene action involved is mainly responsible for the genetic improvement of any crop. Generation means analysis for maize (Zea mays L.) yield and its traits for six generations, i.e. P1, P2 F1, F2, BC1 and BC2 of six crosses evaluated at Karnal. Significant individual and joint scaling tests indicated inadequacy of three parameter models and presence of epistasis in all characters indicating greater genetic variation in parents. However, only shelling percentage in HKI 209 × HKI 163 showed additive-dominance. The presence of duplicate form of non-allelic gene interactions was prominent, except for days to maturity and cob diameter in HKI 325-17AN × HKI 163, cob length in HKI 209 × HKI 163 and shelling percentage in HKI 1332 × HKI 163 where complementary gene action is recorded. It suggests selection from F3 generation onwards for character improvement. Dominance and duplicate type of epistatic effects were found to be more prominent for inheritance than additive effects alone for grain yield/plant, grains/cob, and plant height suggesting the reciprocal recurrent selection or bi-parental mating design to improve in these characters. In crosses where dominance was of major importance, the trait could be successfully utilized for the exploitation of hybrid vigour. Some significant additive and additive × additive effects were recorded in all of these crosses, and therefore gain from selection could be possible, fixable and heritable epistasis could be effectively used in the selection of superior inbred lines.